Preliminary assessment of blood mercury contamination in four African crocodile species - (:unkn) unknown (My University, 2024)
Heavy metal contamination in the environment is an increasingly pervasive threat to the long-term persistence of wildlife. As high trophic level consumers, crocodylians are at substantial risk from bioaccumulation of mercury (Hg). Despite that they are generally well-studied and the focal species of many conservation efforts around the world, little is known about Hg contamination levels in most crocodylians. Here we preliminarily evaluate blood Hg contamination in four African species – Central African slender-snouted crocodile (Mecistops leptorhynchus), African dwarf crocodile (Osteolaemus tetraspis), West African crocodile (Crocodylus suchus), and Nile crocodile (Crocodylus niloticus) – from a diversity of sites and habitats across 5 different countries representing varying degrees of environmental pollution. All of our sampled crocodiles were Hg contaminated and, worryingly, these African crocodiles generally showed the highest levels of Hg contamination of any crocodylian species examined to date. Of most concern was that Hg concentrations were not only highest in M. leptorhynchus, the most threatened amongst our study species, but also in individuals sampled in what are believed to be some of themost remote and pristine natural areas left in Africa – Gabon’s national parks. Our results underscore the need tobetter understand the impact of longstanding petroleum, mining, forestry, and agricultural industries on theentire aquatic food chain throughout much of Africa, including on the threatened species in these habitats andthe human populations that depend on them for their subsistence and livelihoods.
Keywords: African Research